Public Opinion on Treatment and Reuse of Wastewater: Bursa Case Study - Melike Yalılı Kılıç (Doğal Afetler ve Çevre Dergisi)
In this study, the information of wastewater and wastewater treatment plants of Bursa was given and in addition, a survey was conducted to the residents living in Yıldırım, Osmangazi and Nilüfer, which are the central districts of Bursa, about wastewater and reducing the wastewater in the city they live and reusing the wastewater after treatment and thus contributing to protection of water resources. There are 16 questions in the survey consisting of personal information and wastewater data. The survey has been applied to a total of 600 people, 200 from each province. With this survey, it was aimed to create the idea of widening the viewpoint of the people about the wastewater, teaching the grey water concept, and reusing the wastewater from the houses in certain places. As a result of the survey application, it was seen that most of the participants do not reuse the used water and grey water, apply different practices in their homes to reduce wastewater generation, and 40% of the people living in Yıldırım and Osmangazi have no idea about the odor problem in Bursa.